1996
DOI: 10.1111/j.1365-2206.1996.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Children whose parents misuse alcohol: a study of services and needs

Abstract: Despite the fact that many children are affected by parental alcohol misuse, both services and research have largely concentrated on adults. Recently, projects have been set up to assist children, but developments have been piecemeal. This article reports on a qualitative study which learned directly from children, their parents and some young adults what they saw as the effects on children of excessive drinking by one or both parents. The most common consequences were distress at witnessing violence to the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…We are not the first to report experiences of stress and conflicts, tension and threats, coping dilemmas, concealment, uncertainty and worry among family members living with substance abuse (Backett-Milburn et al, 2008 ; Gorin, 2004 ; Haugland, 2005 ; Hill et al, 1996 ; Kroll, 2004 ; Orford et al, 2013 ; Rossow et al, 2015 ; Velleman & Templeton, 2007 ; Wilson et al, 2012 ). A review of research about experiences among children living with domestic violence or parental substance abuse concluded that the trouble at home was often kept as a family secret (Gorin, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We are not the first to report experiences of stress and conflicts, tension and threats, coping dilemmas, concealment, uncertainty and worry among family members living with substance abuse (Backett-Milburn et al, 2008 ; Gorin, 2004 ; Haugland, 2005 ; Hill et al, 1996 ; Kroll, 2004 ; Orford et al, 2013 ; Rossow et al, 2015 ; Velleman & Templeton, 2007 ; Wilson et al, 2012 ). A review of research about experiences among children living with domestic violence or parental substance abuse concluded that the trouble at home was often kept as a family secret (Gorin, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirm research demonstrating unmet needs of families in troubles, disruptions in everyday rituals and routines, and family members trying to find the best way of dealing with the situation (Backett-Milburn et al, 2008 ; Haugland, 2005 ; Mordoch & Hall, 2008 ; Orford et al, 2013 ; Trondsen, 2012 ; Trondsen & Tjora, 2014 ). Roles within these families are distorted, with the children responsible for paying attention and making one's arrangements in accordance with the parent with drinking problems, taking on caring and protective roles within the family (Haugland, 2005 ; Hill et al, 1996 ; Kroll, 2004 ; Vernig, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International research has shown serious consequences for the development of children of alcoholics (4). Co-instantaneous research has shown that the problems of the children are often invisible in the treatment (5)(6)(7).…”
Section: Living With An Alcoholic Parentmentioning
confidence: 99%